The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nin.12268
|View full text |Cite
|
Sign up to set email alerts
|

Marginalization: Conceptualizing patient vulnerabilities in the framework of social determinants of health—An integrative review

Abstract: Scientific advances in healthcare have been disproportionately distributed across social strata. Disease burden is also disproportionately distributed, with marginalized groups having the highest risk of poor health outcomes. Social determinants are thought to influence healthcare delivery and the management of chronic diseases among marginalized groups, but the current conceptualization of social determinants lacks a critical focus on the experiences of people within their environment. The purpose of this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 62 publications
(101 reference statements)
1
157
0
2
Order By: Relevance
“…Furthermore, each discipline has its own conceptual map and scholarly genealogy of this notion. For example, in the nursing science literature, marginalisation was proposed as a nursing theory by Hall et al in 1994 [8,9,10]. It then underwent a progressive transformation which led to the inclusion of additional elements, such as Eurocentrism [11] and then went through a series of expansions integrating scholarship on globalisation, privilege and intersectionality [12].…”
Section: Introduction Materials and Methodsmentioning
confidence: 99%
“…Furthermore, each discipline has its own conceptual map and scholarly genealogy of this notion. For example, in the nursing science literature, marginalisation was proposed as a nursing theory by Hall et al in 1994 [8,9,10]. It then underwent a progressive transformation which led to the inclusion of additional elements, such as Eurocentrism [11] and then went through a series of expansions integrating scholarship on globalisation, privilege and intersectionality [12].…”
Section: Introduction Materials and Methodsmentioning
confidence: 99%
“…Last, research has indicated that limited access to affordable housing is the most acute problem for women, because it forces them to return to living environments in which they are at risk of violence (Bunn, 2018 ; Owen et al, 2017 ). This demonstrates the role of structural factors in partial reentry services, in which women are exposed to an unprotected environment where the interaction of sociopolitical, economic, structural, cultural, and interpersonal circumstances put them at physiological and psychological risk (Baah et al, 2019 ). In an exploratory study of the effects of such health-damaging environments conducted among 204 women in Kansas City jails, Ramaswamy, Kelly, Koblitz, Kimminau, and Engelman ( 2011 ) revealed an association between experiences of violence and incarcerated women’s self-reports of cervical cancer screening and cancer history and treatment.…”
Section: An Intersectional Perspective On the Health Issues Of Justicmentioning
confidence: 98%
“…For example, a newly diagnosed low income cancer patient may spend his/her few life savings on treatments. This process can limit his ability to benefit from treatments and will push the individual further to a marginalized geographical location with limited access to health care services and basic needs (e.g., affordable housing) (Baah, Teitelman, & Riegel, 2019). Crenshaw (1991) charted three foci of intersection as analytical guides for assessment of this interplay.…”
Section: Intersectionality and Intersectional Criminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tailoring a programme to local cultural, health, and belief systems remains a challenge for nongovernmental organisations (NGOs) [8,18,19]. Most broadly, peoples' diverse socioeconomic contexts influence their behaviours, and this diversity needs to be accounted for if public health programmes are to provide agency for patients and improve the impact of interventions [20][21][22]. These challenges are compounded in the low-resource settings of rural areas in developing countries where there is sometimes divergent knowledge about health between participants, and where populations are dispersed and use several different indigenous languages [23,24].…”
Section: Introductionmentioning
confidence: 99%